Contralateral R1 and R2 components of the laryngeal adductor reflex in humans under general anesthesia. (4th August 2017) - Sinclair, Catherine F.; Téllez, Maria J.; Tapia, Oscar R.; Ulkatan, Sedat
Abstract : Objectives: To demonstrate that under total intravenous general anesthesia (TIVA), the contralateral R1 (cRI) and contralateral R2 (cR2) components of the laryngeal adductor reflex (LAR) can be reliably elicited; to determine effects of topical anesthesia and inhalational anesthesia on the LAR; and to discuss how this technique may be utilized to continuously monitor the vagus nerve reflex arc. Study Design: Case series. Methods: Vocal fold mucosa was electrically stimulated via endotracheal tube surface‐based electrodes to elicit a LAR. Responses were recorded using the endotracheal tube electrode contralateral to the simulating electrode for each side. Results: Twenty‐one patients (31 nerves at risk), aged between 28 to 84 years, who underwent thyroid and cervical spine surgeries (4 males, 17 females) were included. cR1 responses were reliably elicited in all patients, and cR2 responses were obtained in 14 patients (66.6%). Mean cR1 latencies ± standard deviation were 22.5 ± 2.5 milliseconds (ms) (left) and 23.4 ± 3.3 ms (right). Mean cR1 amplitudes were 237.9 ± 153.9 microvolts (uV) (left) and 265.0 ± 226.5 uV (right). Mean R2 latencies were 59.8 ± 4.9 ms (left) and 61.8 ± 7.9 ms (right). Intraoperative reversible cR1 amplitude decreases correlated temporally with surgical maneuvers stretching or compressing the RLN or internal branch of the superior laryngeal nerve (iSLN). Inhalational anesthetic agents abolished cR2 and minimized cR1 at mean alveolar concentrations > 0.5. Topical lidocaine significantly reduced LAR amplitude. Conclusion: LAR cR1 and cR2 responses are present in humans under TIVA and may afford some airway protection against aspiration under anesthesia. They are inhibited by inhalational anesthetics and topical lidocaine. Continuous intraoperative iSLN and RLN monitoring are possible using surface‐based endotracheal tube electrodes alone to stimulate and record cR1 responses. Level of Evidence: 4. Laryngoscope, 127:E443–E448, 2017